2018
DOI: 10.1182/bloodadvances.2018019737
|View full text |Cite
|
Sign up to set email alerts
|

Infused wild-type macrophages reside and self-renew in the liver to rescue the hemolysis and anemia of Hmox1-deficient mice

Abstract: Heme oxygenase 1 (HMOX1), the inducible enzyme that catabolizes the degradation of heme into biliverdin, iron, and carbon monoxide, plays an essential role in the clearance of senescent and damaged red blood cells, systemic iron homeostasis, erythropoiesis, vascular hemostasis, and oxidative and inflammatory stress responses. In humans, HMOX1 deficiency causes a rare and lethal disease, characterized by severe anemia, intravascular hemolysis, as well as vascular and tissue damage. Hmox1 knockout (KO) mice reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Increased level of MCP-1 in the livers of HO-1 KO mice resulted in constant recruitment and significantly higher than in WT mice numbers of F4/80 low CD11b high MDMs. It was recently shown that WT bone marrow derived macrophages engraft in the livers of HO-1 KO mice, differentiate into KCs, and self-renew, protecting the recipient for several weeks and potentially for a lifetime [29,55]. In the present study, in WT mice we noted the expansion of KCs 3 days after delivery of the 1 st dose of scAAV9-GFP (their number after the 2 nd vector dose was comparable with untreated mice).…”
Section: Plos Onesupporting
confidence: 76%
“…Increased level of MCP-1 in the livers of HO-1 KO mice resulted in constant recruitment and significantly higher than in WT mice numbers of F4/80 low CD11b high MDMs. It was recently shown that WT bone marrow derived macrophages engraft in the livers of HO-1 KO mice, differentiate into KCs, and self-renew, protecting the recipient for several weeks and potentially for a lifetime [29,55]. In the present study, in WT mice we noted the expansion of KCs 3 days after delivery of the 1 st dose of scAAV9-GFP (their number after the 2 nd vector dose was comparable with untreated mice).…”
Section: Plos Onesupporting
confidence: 76%
“…During episodes of hemolysis, macrophages in the spleen and liver are responsible for detoxifying heme from the extracellular environment. 29,45 To examine the metabolic state of these organ systems in a model of chronic hemolysis, we used Townes SCD transgenic mice, which express human b-globin instead of the endogenous mouse protein. [46][47][48] When compared with mice that expressed normal human hemoglobin (b A mice), mice that expressed sickle hemoglobin (b S mice) had significantly higher levels of free heme in their serum (Figure 7A).…”
Section: Macrophages Undergo Metabolic Adaptation In Clinically Relevant Models Of Heme Clearancementioning
confidence: 99%
“…Insufficient macrophage iron recycling function commonly leads to accumulation of iron in tissues. Non-heme iron increases in Nramp1−/− mice which do not efficiently www.nature.com/scientificreports/ recycle iron from damaged red blood cells 44 , in myeloid specific Fpn1−/− mice due to impaired mobilization from macrophages 45 , in Hmox1−/− mice due to heme toxicity that leads to broad depletion of iron recycling macrophages 21,46 , and Spic−/− mice due to loss of red pulp macrophages 23 . Further, we found the exacerbation of iron restricted erythropoiesis caused by post burn M-CSF neutralization was associated with augmented secretion of G-CSF and IL-6.…”
Section: Discussionmentioning
confidence: 99%